The Decentralization, Devolution and Local Governance Practices in Nepal: The Emerging Challenges and Concerns - Chaudhary, Deepak (Journal of Political Science, 2019)
Nepal has been facing political changes and systems over the decades. Presently Nepal has adopted the unitary federal political system. Under the system, devolution of power is shared to local levels in order to strengthen localism and development. The devolution is a broader concept of decentralization where power and authority are provided to a sub-national level of government constitutionally. This paper discusses the devolution and its implication on local levels that are directly related to local people and grass-roots democracy. The Constitution of Nepal 2015, Local Government Operations Act 2017, Inter Governmental Fiscal Transfer Act 2017 and other sectoral legislation and published related documents are reviewed for this paper. Besides, three numbers of local levels (rural municipalities) are taken as an empirical inquiry to find out the problems and challenges facing by local levels. The Constitution of Nepal 2015 provided enough power and authority to the local levels based on devolution under federalism. Despite that, the inadequacy of laws, and policies, and lacking coordination between local levels and center-province and poor mobilization are major challenges to local levels and the question of good governance and leadership is more pronounced in this regard. The relationship among the center, province and local levels is still debatable. Overall, the present collateral form of local governance is not being well functioned. The effectiveness of Leadership seems to be important to cope with local governance for local development and grass-roots democracy.